Analisis Break Even Point Usaha Peternakan Sapi Perah di Kabupaten Semarang - Ruth Dameria Haloho (Fakultas Pertanian, Universitas Timor, 2021)
This research analyzes the Break-Even Point of smallholder dairy Farming and to know the maintenance of dairy cattle in Semarang Regency. A survey method was used in this research. The sampling technique in this study used the Multistage Random Sampling Method. Respondents studied were 80 dairy farmers. The data obtained were analyzed descriptively and quantitatively. The result showed BEP in Semarang regency based on revenue of IDR 31, 916/day and based on the amount of production of 10.57 liters/day. The average revenue volume of production/ day is 24.88 Liters/day and the average revenue is IDR 70,771/day thus the dairy business is already operating above the Break-Even Point. The maintenance of dairy cows consists of feeding (forage and concentrate) and drinking adlibitum, livestock sanitation is carried out twice a day, 12 months of calving interval, the type of pen is conventional and milking is done twice a day, namely in the morning and evening.